2012
DOI: 10.1002/mrm.24382
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal rotating frame relaxation time measurements in infarcted mouse myocardium in vivo

Abstract: Longitudinal relaxation time in the rotating frame (T1ρ) was measured using continuous wave irradiation in normal and infarcted mouse myocardium in vivo. Significant increase in T1ρ was found after 7 days of infarction when compared with reference myocardium or in myocardium before infarction. Cine MRI and histology were performed to verify the severity of infarction. The time course of T1ρ in the infarct fits better with granulation and scar tissue formation than necrosis and edema. The results of the study s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 31 publications
3
61
0
Order By: Relevance
“…These results correlate well with the increased fibrosis visualized using histology. In a previous study, a similar increase in T 1ρ was found after 7 days of left anterior descending artery occlusion in mice . Together, these results indicate that T 1ρ acts as a general marker for fibrosis which is more widely applicable than for myocardial infarcted tissue only.…”
Section: Discussionsupporting
confidence: 78%
“…These results correlate well with the increased fibrosis visualized using histology. In a previous study, a similar increase in T 1ρ was found after 7 days of left anterior descending artery occlusion in mice . Together, these results indicate that T 1ρ acts as a general marker for fibrosis which is more widely applicable than for myocardial infarcted tissue only.…”
Section: Discussionsupporting
confidence: 78%
“…In our model, no fibrosis was detected on histological analysis, in comparison with a myocardial infarction study on mice in which T 1ρ was found to be associated with fibrosis. 12 Both T 2 and T 1ρ showed similar changes after ischemia, which implies that the processes causing these changes are mainly close to the frequency of~1250 Hz at which T 1ρ is sensitive, and no substantial processes, at least not opposing ones, occur at lower frequencies. T 2 and T 1ρ also revealed a significant difference (p < 0.01) between relaxation times in early regenerative areas compared with areas of normal tissue and late regeneration.…”
Section: Discussionmentioning
confidence: 76%
“…Post‐ischemic increases in T 2 have also been reported in previous studies of hind limb ischemia and ischemia–reperfusion injury, but only a few studies have implemented T 1ρ in skeletal muscle imaging. In our model, no fibrosis was detected on histological analysis, in comparison with a myocardial infarction study on mice in which T 1ρ was found to be associated with fibrosis . Both T 2 and T 1ρ showed similar changes after ischemia, which implies that the processes causing these changes are mainly close to the frequency of ~1250 Hz at which T 1ρ is sensitive, and no substantial processes, at least not opposing ones, occur at lower frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…The mFI imaging is based on T 1 ρ dispersion contrast, rather than the absolute T 1 ρ contrast. The latter has been reported by several groups to show up to a 1-fold higher T 1 ρ value for myocardial scar tissue induced by MI [12,13,20]. For other regions with less collagen content, such as the border zone of the infarct, the amount of increase in T 1 ρ is much less, making the distinction and quantification of differences in fibrosis more problematic.…”
Section: Discussionmentioning
confidence: 80%
“…This contrast approach measures spin-lattice relaxation time in the rotating frame at a spin-lock amplitude B 1 [11]. In myocardial muscle, T 1 ρ increased up to 2-fold in regions of chronic, non-reperfused MI (primarily replacement fibrosis or scar), in comparison with remote normal myocardial tissue [12,13]. A recent report by van Oorschot et al demonstrated a good correlation of myocardial T 1 ρ and ECV values in 20 patients with dilated cardiomyopathy (Pearson r = 0.66) [14].…”
Section: Introductionmentioning
confidence: 99%